Adaptasi Penyandang Disabilitas di Lingkungan Masyarakat (Studi Kasus Penyandang Disabilitas Netra Pertuni Kota Makassar) - Fadhilah, Arwina; Tahir, Heri; Manda, Darman (Universitas Negeri Makassar, 2021)
The study aims to discover: (i) the socialization process experienced by visual impairments disabilities of Pertuni, (ii) the forms of adaptation visual impairments disabilities in the community, and (iii) the factors which influence the adaptation of visual impairments disabilities in the community. This study employed a qualitative descriptive approach with purposive sampling technique with 9 informants. Data collection techniques employed observation, interview, and documentation. The data analysis technique used three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of the study: (i) the visual impairments disabilities in the socialization process are essential attitudes, values, norms, and behaviors that can be applied in their lives to be able to adapt and participate effectively in society, (ii) the form of adaptation of visual impairments disabilities produces conformity which is an effort to adapt to visual impairments disabilities by following the prevailing methods in society, and self-isolation as an alternative at the beginning when visual impairment disabilities are unable to accept their condition (self isolation), and (iii) the factors that influence the adaptation of visual impairments disabilities are the reinforcement factors for the needs of physiology,Â sense of security, compassion, the needs for appraisal, and self-actualization. The inhibiting factor is a stigma, where the community still gives a negative stigma to the existence of visual impairments disabilities persons.